Interpretation of Heart Rate Variability: The Art of Looking Through a Keyhole - Karemaker, John M. (Frontiers in Neuroscience, 2020)
The heart may be a mirror of the soul, but the human mind is more than its heart rate variability (HRV). Many techniques to quantify HRV promise to give a view of what is going on in the body or even the psyche of the subject under study. This “conceptual analysis” paper gives, on the one hand, a critical view on the field of HRV-analysis and, on the other hand, points out the direction of future applications. In view of the inherent variability of HRV and the underlying processes, as lined out here, the best use may be found in serial analysis in a subject/patient, to find changes over time that may help in early discovery of developing pathology. Not every future possibility is bright and shining, as demonstrated in a fictional diary excerpt from a future subject, living in a society geared towards preventive medicine. Here implanted biochips watch over the health of the population and artificial intelligence (AI) analyses the massive data flow to support the diagnostic process.